Effect of the Different Soil Types on Chrysanthemum Cut Flower Quality - Herni Shintiavira; Endang Sulistyaningsih; Aziz Purwantoro; Rani Agustina Wulandari (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Cultivating annual crops in the high upland has the potential to increase avalanche and land erosion. Therefore, chrysanthemum extensification from high upland to medium upland can create sustainable agriculture. The differences between high upland and medium upland are microclimate and soil type. Meanwhile, the effect of soil type between the high upland and the medium upland on the chrysanthemum spray type quality is unknown. The study aimed to determine the effect of different soil types on the quality of chrysanthemums when planted in high upland. The study used a split plot design with two factors. The first factor was the type of soil, such as Andosol from the high upland and Latosol from the medium upland. The second factor was the chrysanthemum varieties, such as Yastayuki (white flower), Arosuka Pelangi (yellow flower) and Socakawani (red flower). The results showed that both Andosol and Latosol soil types could produce the same quality of chrysanthemum in all varieties when planted in high upland. The quality aspects of chrysanthemum were the plant height, the stem diameter, the number of flowers and flower color. Consequently, we could extend the cultivation of chrysanthemum in medium upland by using Latosol type soil.